INCIDENCE OF THERAPEUTIC OPENING OF FALLOPIAN TUBES DURING HYSTEROSALPINGOGRAPHY - Shahnawaz, Mohammad; Ibrahim, Mohammad (Journal of Ayub Medical College Abbottabad, 1995)
A study of 20 married primarily infertile female patients, aged 22-30 years, without any other constitutional disease and with husbands having normal sperm counts, to determine the incidence of therapeutic opening of the fallopian tubes during hysterosalpingography. Hysterosalpingography was performed using water soluble contrast medium with an improved method of upto 3 consecutive injections during a single examination. In these patient's fallopian tubes opened up on repeated injections of 10-20 ml of contrast medium. 20 patients were followed-up to monitor the incidence of conception. 25% conceived within the first three months of the procedure. 10% conceived in six months' time. 35% of these started other medications, hence were excluded from the study. In 30% opening of the fallopian failed to yield any benefit. Study brings to light the therapeutic advantages of hysterosalpingography in addition to its known diagnostic value.